Tinjauan Yuridis Cyber Espionage Berdasarkan Hukum Internasional - Aldo Rahmandana (Jurist-Diction, 2021)
AbstractDue to the rapid transformation of technology causing a subliminal changes on how states spy upon each other. With the help of technology and cyber infrastructure, states tend to use cyber technology as its main facility to conduct an espionage towards other states. Cyber espionage has come to represent national security and economic threat, due to all the classified information that already been massively stolen by another country. The aim of this research paper is to analyze and clarify pertaining the role of International law specifically towards this kind of act of espionage, and perceive the state responsibility of perpetrator which is states. It can be concluded that cyber espionage does not per se regulated under international law, but its lawfulness depends on the way in which it operation carried out may violate specific international conventions or any other international law principles.Keywords: Cyberlaw; Cyber Espionage; International Law.AbstrakPesatnya perkembangan teknologi dan digitalisasi mengakibatkan terjadinya perubahan metode dan cara dalam pelaksanaan tindakan spionase oleh negara terhadap negara lain guna mengumpulkan fakta dan informasi yang berkaitan dengan perkembangan politik, ekonomi, teknologi, dll melalui kapabilitas teknologi siber atau kerap disebut sebagai cyber espionage. Tujuan dari penelitian ini adalah untuk menganalisis terkait peranan hukum internasional dalam mengatur tindakan tersebut dalam tataran internasional dan bagaimana pertanggungjawaban dari negara pelaku tindakan cyber espionage. Hasil dari penelitian ini menyimpulkan bahwa belum ada konvensi international khusus yang mengatur mengenai cyber espionage sehingga tindakan cyber espionage itu sendiri merupakan tindakan yang masih belum diatur secara international.Kata Kunci: Hukum Siber; Cyber Espionage; Hukum Internasional.